Dolor torácico en el Servicio de Urgencia - Abiuso A., Natalia; Brinkmann B., Manuela; Espinoza Z., Carolina (Revista Hospital Clínico Universidad de Chile, 2014)
According to the literature, chest pain corresponds to an estimate of 5 to 9% of presenting complaints in Emergency Departments (ED) in the United States. In spite of the high rate of admission, there is still a 0,4 to 4% of patients who are discharged from an ED with a missed Acute Myocardial Infarction. Diagnostic etiologies range from benign to life-threatening conditions, so there is the need for a clinical approach that is both safe and cost-effective. The diagnostic strategies are based on three elements: anamnesis and physical examination, Electrocardiography and chest X-ray. This article presents an Emergency Medicine-oriented perspective in the hopes of offering to the physician a strategie focused in ruling out life- threatening conditions in the first place and then define patient disposition in an efficient and safe manner.